The smallest known Devonian tetrapod shows unexpectedly derived features. - Ahlberg, Per E; Clack, Jennifer A (The Royal Society, 2020)
A new genus and species of Devonian tetrapod, Brittagnathus minutus gen. et sp. nov., is described from a single complete right lower jaw ramus recovered from the Acanthostega mass-death deposit in the upper part of the Britta Dal Formation (upper Famennian) of Stensiö Bjerg, Gauss Peninsula, East Greenland. Visualization by propagation phase contrast synchrotron microtomography allows a complete digital dissection of the specimen. With a total jaw ramus length of 44.8 mm, Brittagnathus is by far the smallest Devonian tetrapod described to date. It differs from all previously known Devonian tetrapods in having only a fang pair without a tooth row on the anterior coronoid and a large posterior process on the posterior coronoid. The presence of an incipient surangular crest and a concave prearticular margin to the adductor fossa together cause the fossa to face somewhat mesially, reminiscent of the condition in Carboniferous tetrapods. A phylogenetic analysis places Brittagnathus crownward to other Devonian tetrapods, adjacent to the Tournaisian genus Pederpes. Together with other recent discoveries, it suggests that diversification of 'Carboniferous-grade' tetrapods had already begun before the end of the Devonian and that the group was not greatly affected by the end-Devonian mass extinction.